(untitled) (Tanzania Medical Journal, 2024)
Background Chronic rhinosinusitis (CRS) is a common and significant health problem with negative impact on quality of life and socioeconomic welfare of patients. Objective This study associated the clinical features of CRS with findings of computed tomography of paranasal sinuses (CT PNS). Methodology This hospital based descriptive cross-sectional study recruited 126 participants aged 10 years and above who fulfilled the criteria of Chronic Rhinosinusitis according to rhinosinusitis symptom inventory (RSI) developed by the American Academy of Otorhinolaryngology Head and Neck Surgery from October 2019 to January 2020. Data was analyzed using SPSS program version 26 and a p value of < 0.005 was considered to be statistically significant. Results Most participants were in age group 31 - 40 (23.8%) years, age ranged from 12 years to 77 years. Females were 61.9%. The commonly reported symptom was nasal obstruction/congestion (89.7%). Nasal endoscopy revealed secretion (thin and/or thick) in all participants (100%), with nasal polyps seen in 61.9% of them. Computed tomography of PNS showed opacification was frequent in maxillary sinus (93.7%). Bone thickening was seen in 61.1% of the patients. Anatomical variations were seen in 52.4% of participants; of which deviated nasal septum (56.1%) was the most common. There was a strong correlation between CT scan (Lund Mackay) score and nasal endoscopy (Lund Kennedy) score with Pearson correlation coefficient of 0.66. Sensitivity and positive predictive value were 100% and 96% respectively. Conclusion and Recommendation Nasal endoscopy and CT scores have a strong correlation; the use of nasal endoscopy and/or CT scan supports in making specific diagnosis and treatment.